The Role Of Waqf Institutions After The Enactment Of Law Number 41 Of 2004 - Kurniasih, Dewi; Prastiwi, Endah (Master of Sharia Economics Program, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
In terms of Wakaf governance in Indonesia, Act No. 41 of 2004 on Wakaff changed the perspective. Since wakaf is the teaching of Islamic law that eventually became part of the tradition of society, it was initially managed in a simple and family-friendly manner. Later, it developed into a credible, professional, and effective institutional governance. In this study, the library institute uses a normative and historical jurisprudential approach. The main source of law, Legislative Decree No. 41 of 2004 on Wakaf, is reinforced by secondary law sources, such as books, legal journals, and doctrines of law. And in its history, the Wakaf institution has made a significant contribution to the social, economic, and cultural well-being of Islam. Wakaf is also one of the possible solutions to the need for funds to address so many problems of the people individually as well as the Islamic institutions.